Pulmonary hypertension associated with congenital portosystemic shunts as a new form of portopulmonary hypertension in children and adults - I. M. Miklashevich; E. A. Potrokhova; D. A. Morozov (Кардиоваскулярная терапия и профилактика, 2024)
Pulmonary arterial hypertension (PAH) associated with portal hypertension, or portopulmonary hypertension, is a severe, life-threatening complication of portal hypertension and/or portocaval shunt surgery. Congenital portocaval shunts (CPSSs) are rare vascular anomalies of the portal system, leading to severe pathophysiological reactions and multisystem damage, including PAH, liver nodules, cognitive, metabolic, immune, hematological and hormonal disorders. Severe cardiopulmonary complications are detected in more than a third of patients with CPSSs, which is the main cause of their death. The article describes the pathophysiology, clinical characteristics, diagnostic features and possibilities of modern targeted therapy for CPSS-associated PAH. Patients with CPSS-associated PAH require comprehensive specialized care in an expert center. For long-term successful management of patients, continuous targeted therapy for PAH, in combination with surgical treatment of CPSSs, is crucial.